The Capital Market - Andrew F. Newman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper offers an account of the occupational choice among wage work, self-employment and entrepreneurship which contrasts with the "Knightian" one based on risk attitudes. As shown by example, the latter can lead to perverse results. We propose a model in which imperfect capital markets arising from costly output verification cause the cost of capital to decline with an agent's wealth. Employment contracts, which require costly labor monitoring are then viewed as a substitute for financial contracts. The prevalence of employment contracts (as distinguished from self-employment) then depends on (1) how effective is the labor monitoring technology as a substitute for output verification in the capital market; and (2) how unequal is the distribution of wealth.
Keywords: 330